Miscarriage Rate Is High With Frozen-Thawed Blastocysts Arising From Poor-Quality Cleavage Stage Embryos - Xia, Lan; Zhao, Shen; Xu, Huiui; Wu, Xian; Zhang, Aijun; Niu, Zhihong (Frontiers in Endocrinology, 2020)
Embryos with low morphological scores can still develop into the blastocyst stage and result in good clinical outcomes. However, no studies have reported the possible effects of transferring cryopreserved blastocysts developed from poor-quality cleavage embryos on pregnancy and perinatal outcomes. In this retrospective study, the clinical value of transferring blastocysts derived from day 3 poor-quality cleavage embryos during in vitro fertilization and embryo transfer procedures was evaluated. According to the quality of embryos on day 3 from which the transferred blastocyst originated, patients were divided into three groups: poor-quality (111 cycles, group A), good-quality (235 cycles, group B), and top-quality (119 cycles, group C). Group A experienced the highest miscarriage rate (30.16%) compared to group C (12.5%) (P = 0.03). The clinical pregnancy rate and live birth rate were not significantly different among the three groups. However, good blastocyst originated from top day 3 embryos resulted in higher live birth rate. Of the 218 live births, no differences in obstetric and perinatal outcomes were noted among the three groups. The results showed that extended culture of poor-quality cleavage embryos could resulted in favorable clinical pregnancy rates but a higher incidence of miscarriages. Meanwhile, the risk of adverse perinatal outcomes was not increased.